Growth Performance, Cytokine Expression, and Immune Responses of Broiler Chickens Fed a Dietary Palm Oil and Sunflower Oil Blend Supplemented With L-Arginine and Varying Concentrations of Vitamin E - Khatun, Jannatara; Loh, Teck Chwen; Foo, Hooi Ling; Akit, Henny; Khan, Kabirul I. (Frontiers in Veterinary Science, 2020)
This study set out to examine the combined effects of the supplementation of a dietary palm oil (PO) and sunflower oil (SO) blend, 0.25% L-Arginine (L-Arg), and different levels of vitamin E (Vit E) on growth performance, fat deposition, cytokine expression, and immune response in broilers. A total of 216 one-day-old male broiler chicks (Cobb500) were randomly distributed into six dietary groups as follows: Diet 1: 6% palm oil (negative control); Diet 2: PO and SO blend (4% palm oil and 2% sunflower oil) + 0.25% L-Arg (positive control); Diet 3: ( PO and SO blend + 0.25% L-Arg) + 20 mg/kg Vit E; Diet 4: (PO and SO blend + 0.25% L-Arg) + 50 mg/kg Vit E; Diet 5: (PO and SO blend + 0.25% L-Arg) + 100 mg/kg Vit E; and Diet 6: (PO and SO blend + 0.25% L-Arg) + 150 mg/kg Vit E. Weight gain and serum IgG and IgM increased while feed conversion ratio, fat deposition, and plasma cholesterol decreased in broilers fed Vit E with the oil blend and L-Arg, compared to those fed the negative control (Diet 1). Expression of IFN and TNF-α were reduced, whereas TGF-ß1 was up-regulated as the level of Vit E increased in the broiler diets. In summary, the combination of oil blend, L-Arg, and Vit E at a level of 50 mg/kg increased the performance and altered the expression of cytokines that may positively influence immune function in broiler chickens.